Cortical plasticity in perceptual learning demonstrated by transcranial magnetic stimulation. - Walsh, V; Ashbridge, E; Cowey, A (1998)
Performance on a wide range of perceptual tasks improves with practice. Most accounts of perceptual learning are concerned with changes in neuronal sensitivity or changes in the way a stimulus is represented. Another possibility is that different areas of the brain are involved in performing a task while learning it and after learning it. Here we demonstrate that the right parietal cortex is involved in novel but not learned visual conjunction search. We observed that single pulse transcranial magnetic stimulation (TMS) to the right parietal cortex impairs visual conjunction search when the stimuli are novel and require a serial search strategy, but not once the particular search task has been learned. The effect of TMS returns when a different, novel, serial search task is presented.